Factors influencing the survival of patients with end stage renal failure, who had been chronically hemodialyzed at Dr. Sardjito General Hospital. - Suhardi Suhardi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
An observational study on factors influencing the survival of 40 patients with end stage renal failure, who had been chronically hemodialyzed at Sardjito General Hospital was performed. The major causes of end stage renal failure in these patients were: chronic glomerulonephritis (22 patients); Diabetes mellitus (9 patients); renal stones (5 patients) and miscellaneous (4 patients). Seventeen of those 40 patients had poor protein intake (42,5%) while the other 23 patients had sufficient protein intake. Patients having sufficient protein intake proved to have better survival than those having poor ones who died more in the first year from intractable congestive heart failure with sepsis. Meanwhile other factors such as the control of hypertension, causes of end stage renal failure and the age of patients were not proved to influence the patients survival. Survival rates of the patients with end stage renal failure who had chronic hemodialysis at Sardjito General Hospital from 1 January 1986 to 31 December 1991 was 62.2% in the first year and 45% in the second year. Most patients died in the first year from intractable congestive heart failure with sepsis, and might becaused by poor protein intake,Key words : end stage renal failure - chronic hemodialysis - protein intake - survival rate.